Thymus-like phenotype in benign lymphoepithelial neoplasms of salivary glands: clinicopathological and molecular characterization and reappraisal of relationship to non-sebaceous lymphadenoma - Agaimy, Abbas; Laco, Jan; Schubart, Christoph; Stöhr, Robert; Tögel, Lars; Ihrler, Stephan (Virchows Archiv, 2025)
Benign lymphoepithelial tumors of salivary glands had been restricted to sebaceous and non-sebaceous (NSLA) lymphadenomas. However, salivary neoplasms recapitulating carcinoma showing thymus-like elements (CASTLE) have been the subject of recent case reports. We reviewed clinicopathological, immunohistochemical, and molecular findings in 20 salivary gland tumors with thymus-like phenotype (18 histologically benign and two with malignant component). Original diagnoses were NSLA (n = 11) and unclassified thymus-like lymphoepithelial neoplasms (n = 9). Patients were 13 males and 7 females aged 28 to 83 years (median, 61). All tumors originated in the parotid with a median tumor size of 2.7 cm. A cystic component was noted in eight cases (40%). Histologically, the tumors were composed of large squamoid cells with indistinct cell borders, forming large irregular branching and anastomosing aggregates within lymphoid stroma with Hassall corpuscle-like structures and intraepithelial sprinkling of lymphocytes. All tumors were diffusely positive for p63/p40 and CK5/CK14. CD5 and CD117 were expressed in 13/20 (65%) and 15/19 (79%) cases, respectively. The malignant component in two cases showed lower CD5/CD117 expression. Targeted DNA sequencing revealed pathogenic/likely pathogenic CYLD mutations in 4/7 cases (57%). One case each had a mutation in TAF1 + WISP3, DNMT3A, and BCOR. Targeted RNA sequencing revealed a YAP1::MAML2 fusion in 1/7 cases. This is the first systematic study addressing the concept of thymus-like phenotype in benign lymphoepithelial salivary gland tumors, showing that the majority of NSLAs (65%) belong to this poorly characterized category. Frequent CYLD mutations in these histologically distinct tumors represent a novel addition to the spectrum of CYLD-mutated salivary neoplasms.
CRIS-Team Scopus Importer:2025-09-26
Keywords: EBV; Lymphadenoma; Molecular profiling; Next-generation sequencing; Thymic carcinoma; Thymoma; WHO classification